Internationalizing Campus Partners - Koseva, Plamena (Journal of International Students, 2018)
The available discourse on how international students’ needs and expectations are accommodated in U.S. higher education institutions is extensive while the corresponding research on how International Services’ Staff (ISS) are prepared for the challenge is limited. The purpose of this essay was to research the personal, academic, and professional background of individuals working in International Services Offices (ISOs) nationwide and identify issues that are not sufficiently addressed. The survey allowed for the collection of data on the training and experience of International Services Staff as well as the methods and strategies used to effectively communicate with international students. Upon discussion of the findings and their significance, the author proposes future recommendations through the implementation of a practical training module.